The Imami Shiite Doctrine about the Companions of the Best of Creatures (Prophet Muhammad PBUH) - Jedayeh, Nabeel Ahmed Hussein (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed at clarifying and explaining the image of the honorable companions in the perspective of the Imami Shi’a. The study concluded that the Shiites are infidelizing the majority of companions, and they prefer to insult and curse them . They consider that this is the way by which they could gain the pleasing of Allah Almighty .